(In)seguridad alimentaria en América Latina y el Caribe. Discusión sobre los datos de producción y disponibilidad de alimentos de la FAO y las políticas públicas en Brasil - Archanjo, Maria de Fátima; Centro de Investigaciones y Estudios Superiores en Antropología Social-Occidente, Guadalajara, Jalisco,México.; Cardoso , Jõao Luiz, Elaine Borghi (2014)
Based on a food and nutrition security approach, this paper analyzes the characteristics of food production and availability in Latin America and the Caribbean. It also examines the intrinsic public policies and, even thought it specifically focuses on Brazil, it attempts to reach conclusions that apply to the whole of Latin America in order to guide actions that strengthen the human right to adequate nutrition. FAO’s Data for the period 1999-2001 shows disparities, which include a vulnerable dependence on international trade, that hinder the viability of agro-alimentary patterns compatible with an adequate nutrition and the concept of sustainable development.